2010
DOI: 10.1021/es902784x
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Utilization of Greenhouse Gas in a Gas-to-Liquids Process Combined with Carbon Dioxide Reforming of Methane

Abstract: A process model for a gas-to-liquids (GTL) process mainly producing Fischer-Tropsch (FT) synthetic oils has been developed to assess the effects of reforming methods, recycle ratio of unreacted syngas mixture on the process efficiency and the greenhouse gas (GHG) emission. The reforming unit of our study is composed of both steam reforming of methane (SRM) and carbon dioxide reforming of methane (CDR) to form syngas, which gives composition flexibility, reduction in GHG emission, and higher cost-competitivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 13 publications
0
29
1
Order By: Relevance
“…Although the CDR reaction, which can produce syngas having a stoichiometric ratio of H 2 /CO of 1.0, seems to be an effective way to utilize CO 2 directly, it is not yet well established for an industrial application due to the negative characters of sever coke formation and catalyst deactivation and so on. Therefore, steam reforming of methane (SRM), which can produce syngas with a stoichiometric molar ratio of H 2 /CO around 3, has been received much attention due to its possible industry application [6][7][8]. In addition, the combined CDR and SRM, which is called as combined steam and CO 2 reforming with CH 4 (CSCR), has been also largely investigated as an alternative reforming reaction of SRM by producing the syngas having a molar ratio of H 2 /CO around 2, which has been known to be a proper composition for the subsequent application to the Fischer-Tropch synthesis and methanol (or dimethyl ether) synthesis reaction and so on [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the CDR reaction, which can produce syngas having a stoichiometric ratio of H 2 /CO of 1.0, seems to be an effective way to utilize CO 2 directly, it is not yet well established for an industrial application due to the negative characters of sever coke formation and catalyst deactivation and so on. Therefore, steam reforming of methane (SRM), which can produce syngas with a stoichiometric molar ratio of H 2 /CO around 3, has been received much attention due to its possible industry application [6][7][8]. In addition, the combined CDR and SRM, which is called as combined steam and CO 2 reforming with CH 4 (CSCR), has been also largely investigated as an alternative reforming reaction of SRM by producing the syngas having a molar ratio of H 2 /CO around 2, which has been known to be a proper composition for the subsequent application to the Fischer-Tropch synthesis and methanol (or dimethyl ether) synthesis reaction and so on [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the combined CDR and SRM, which is called as combined steam and CO 2 reforming with CH 4 (CSCR), has been also largely investigated as an alternative reforming reaction of SRM by producing the syngas having a molar ratio of H 2 /CO around 2, which has been known to be a proper composition for the subsequent application to the Fischer-Tropch synthesis and methanol (or dimethyl ether) synthesis reaction and so on [8]. The CSCR reaction is composed with the following characteristic reactions such as SRM, CDR, and water-gas shift (WGS) or reverse WGS (RWGS) reaction [4][5][6][7][8][9]; …”
Section: Introductionmentioning
confidence: 99%
“…In view of the production of useful chemicals and synthetic fuels, since CDR gives a low H 2 /CO ratio of around 1, the combination of SRM and CDR reactions is an appropriate way to produce syngas which is suitable for methanol or Fischer-Tropsch synthesis reactions which require H 2 /CO ratio of around 2 [9,10]. This reaction, so-called combined steam and carbon dioxide reforming of methane (SCR), recently receives the increased attention from the viewpoint of environmental and efficient resource utilization issues because it would facilitate CO 2 containing natural gas or stranded gas [11,12]. The three representative reforming reactions such as CDR, SRM and SCR could be categorized as follows:…”
Section: Introductionmentioning
confidence: 99%
“…A recent simulation showed that zero emission of CO 2 can be obtained with recycling of unreacted syngas. [112] A recent study [113,114] also proposed tri-reforming as a suitable approach to increase the energy efficiency of fossil-fired power plants (integrated tri-reforming power plants, ITRPPs). Similar approaches were proposed for applications combined to gas turbine power plants [115] or for coke/coal gasification combined with lime carbonation.…”
mentioning
confidence: 99%